Маркетинговий механізм взаємодії вищих навчальних закладів і підприємств: інноваційний підхід - Тугай, А. М.; Гойко, А. Ф.; Єлішевич, М. А. (Ways to Improve Construction Efficiency, 2013)
Focuses on the problems of high school students innovative teaching competency-based approach. Analyzes the marketing mechanism of interaction of the university and enterprises in training competitive specialists.